2014
DOI: 10.1603/ec14008
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Broadcast Baiting on Abundance Patterns of Red Imported Fire Ants (Hymenoptera: Formicidae) and Key Local Ant Genera at Long-Term Monitoring Sites in Brisbane, Australia

Abstract: In 2001, the red imported fire ant (Solenopsis invicta Buren) was identified in Brisbane, Australia. An eradication program involving broadcast bait treatment with two insect growth regulators and a metabolic inhibitor began in September of that year and is currently ongoing. To gauge the impacts of these treatments on local ant populations, we examined long-term monitoring data and quantified abundance patterns of S. invicta and common local ant genera using a linear mixed-effects model. For S. invicta, prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…McNaught et al . () showed that the baits had little effect on the local ant fauna and only one genus, Pheidole , was affected in a similar way to Red Imported Fire Ant. In addition, Pheidole spp.…”
Section: Evaluating Success and Lessons Learnedmentioning
confidence: 98%
See 3 more Smart Citations
“…McNaught et al . () showed that the baits had little effect on the local ant fauna and only one genus, Pheidole , was affected in a similar way to Red Imported Fire Ant. In addition, Pheidole spp.…”
Section: Evaluating Success and Lessons Learnedmentioning
confidence: 98%
“…The baits used by the programme contain pyriproxyfen and methoprene; these chemicals have been in use worldwide for many years and known environmental side effects are minimal if used according to the labels. McNaught et al (2014) showed that the baits had little effect on the local ant fauna and only one genus, Pheidole, was affected in a similar way to Red Imported Fire Ant. In addition, Pheidole spp.…”
Section: Restorationmentioning
confidence: 99%
See 2 more Smart Citations
“…Repeated baiting is required to ensure that fire ant colonies are exposed to a sufficient level of pesticide over a sufficient duration for the colonies to die (McNaught et al. ). The high frequency of repeat treatments reflected uncertainty about the mortality of baiting in Australian conditions.…”
Section: The Queensland Fire Ant Eradication Programmentioning
confidence: 99%